Zinc suppresses Stat3-driven IL-6 production in primary mouse adipocytes - Chung, Hak; Eom, John; Damen, Michelle SMA; Stankiewicz, Traci E.; Sawada, Keisuke; Alarcon, Pablo C.; Ulanowicz, Cassidy J.; Wayland, Jennifer L.; Deepe, George S.; Divanovic, Senad (Frontiers in Immunology, 2026)
Uncontrolled inflammatory cytokine production promotes pathogenesis of various chronic diseases. Zinc (Zn) regulates immune cell inflammatory cytokine production. However, the influence of Zn on the inflammatory properties of non-immune cells known to contribute to disease pathogenesis is not well understood. Adipocytes respond to various immunological stimuli by activating inflammatory pathways and secreting inflammatory cytokines. Here, we investigated the impact of Zn on adipocyte inflammatory vigor. We show that treatment of primary mouse adipocytes with Zn, in the form of Zn pyrithione, restricted their toll-like receptor ligand-driven IL-6 production. Mechanistically, IL-6 secreted from adipocytes functions in an autocrine fashion to activate the Stat3 pathway and amplify IL-6 production via a positive feedback loop. Notably, Zn treatment of adipocytes suppressed Stat3 signaling activation to break the positive feedback loop and subsequent expression of IL-6 and its receptor genes (Il6st, Il6ra). Collectively, our findings uncover a novel inhibitory role for Zn in non-immune cell, specifically adipocyte, IL-6 production. These findings invoke a potential role of Zn in the regulation of adipocyte-associated chronic inflammation and disease pathogenesis.